Reconciling Islam and Human Rights: A Narrative Review of Reform, Resistance, and Realignment - Pramasto, Arafah (Sinergi International Journal of Islamic Studies, 2024)
The intersection of Islam and human rights has become an increasingly contested and vital area of academic inquiry. This narrative review aims to critically examine how Islamic jurisprudence interacts with international human rights principles, particularly in Muslim-majority societies. Using a multidisciplinary methodology, literature was collected from major academic databases including Scopus, Google Scholar, JSTOR, PubMed, and Web of Science. Keywords such as "Islam and human rights," "Sharia law," and "Islamic justice" guided the search, with inclusion criteria focused on peer-reviewed sources published between 2000 and 2024. Findings indicate that social determinants, economic disparities, and institutional frameworks significantly influence how human rights are interpreted and applied in Islamic contexts. Gender inequality, religious minority marginalization, and political resistance are prevalent challenges linked to traditionalist readings of Islamic law. Conversely, reformist movements advocating reinterpretation through concepts like Wasatiyyah and maqāṣid al-sharīʿah illustrate a viable pathway to harmonize Islamic teachings with human rights norms. Case studies from Morocco and Afghanistan exemplify the critical role of political will and governance in shaping rights outcomes. The review highlights systemic and structural barriers in both Muslim-majority and non-Muslim-majority contexts and offers comparative insights into potential policy responses. Legal harmonization, community engagement, education, and interfaith dialogue are emphasized as key strategies. The study concludes by calling for more empirical research and pluralistic, interdisciplinary approaches to enhance the discourse on Islam and human rights globally.